SYMBOLIC MEANING AND LOCAL WISDOM EDUCATION OF THE TRADITIONAL PERFORMING ARTS REOG PONOROGO - Septian Refvinda Argiandini; Sumarwati Sumarwati; Raheni Suhita (Proceedings of the 1st International Conference on Social Science (ICSS), 2023)
Reog Ponorogo is one of the many traditional cultural arts in Indonesia. Artshow Reog in Ponorogo has several versions. Starting from the Wengker, Batarakahtong, and Bantarangin. This research focuses on the traditional performing arts version of Reog PonorogoBantarangin. This research aims to determine the specifics of the educational value of local wisdom and the symbolic meaning of the Reog Ponorogo version of the performing arts Bantarangin. In the Bantangi version, there are five main characters, namely, Klanasewandono, Warok, Jathil, Bujangganong, and Singobarong. The research design used is descriptive qualitative with a semiotic approach. The data collection techniques used were observation, interviews, and documentation. The research results show that art show Tradisional Reog Ponorogo has values of wisdom local farm mark religiosity, leadership, cooperation, and manners. Meanwhile, the symbolic meaning of performing arts traditional Reog Ponorogo reflects the environmental value system of the Ponorogo people, symbolized by the dance movements, attributes, and costumes used by Reog Ponorogo players. The existence of performing arts can be formulated as educational development wisdom local for students. Local wisdom education is currently very necessary to shape student character according to the objectives of the Merdeka curriculum. Through profile-strengthening program lessons Pancasila (P5), value wisdom local and symbolic meaning can be used as an alternative reference for developing Indonesian language teaching discussions about the skills of writing works of fiction with the theme of local wisdom